Phosphorylation of STAT3 correlates with HER2 status, but not with survival in pancreatic ductal adenocarcinoma - Koperek, Oskar; Aumayr, Klaus; Schindl, Martin; Werba, Gregor; Soleiman, Afschin; Schoppmann, Sebastian; Sahora, Klaus; Birner, Peter (APMIS : acta pathologica, microbiologica et immunologica Scandinavica, 2014)
Activation of signal‐transcriptional factor signal transducer and activator of transcription 3 (STAT3) is associated with more aggressive behaviour in a variety of human malignancies. As selective STAT3 inhibitors exist, this protein might represent a novel therapeutic target. Although STAT3 seems to play an important role in progression of pancreatic ductal carcinoma (PDAC), only few data on this subject exist. The aim of our study was the investigation of STAT3 activation and its correlation with its possible regulator HER2. Expression of tyrosine‐705 phosphorylated STAT3 (pSTAT3) was determined immunohistochemically in 79 PDACs. HER2 status assessed by immunohistochemistry and double colour silver in situ hybridization was available from a previous study. PSTAT3 expression was seen in 33 (41.8%) patients. Six patients were scored as HER2 positive having strong correlation with pSTAT3 expression (p = 0.004, Fisher′s exact test). No association of pSTAT3 expression with patients′ age, tumour staging and grading, perineural invasion of tumour cells or survival time was seen. pSTAT3 is frequently expressed in PDAC. Nevertheless, its immediate clinical relevance seems to be low. However, further research needs to determine whether STAT3 status in PDAC is predictive for the response to novel targeting therapies.